Effect of aqueous tetrapleura tetraptera (african porridge fruit) on carcass characteristics and organ weights of broiler chickens (2014)
This study was carried out to determine the effect of Aqueous Tetrapleura tetraptera on carcass value and organ weights of broiler chickens. One hundred and fifty day old Arbor acre broiler chicks were randomly allotted to five treatments having 30 birds each, each group had five replicates with six birds each. Treatment 1 (the control) had no additive, treatment 2 had antibiotics, treatments 3, 4 and 5 had 3ml, 6ml and 9mls of Tetrapleura tetraptera extract respectively in their water. Results indicate that percentage carcass weights of the broilers were significantly influenced by the addition of extracts of Tetrapleura tetraptera in their diets for breast muscle range from (22.81-28.42) and wings from (11. 12- 12.80) % of Dressed Weight (DIV) respectively. It also shows that there were significant differences (p≤0.05) in the data recorded for liver (3.25-4.24) and gizzard(4. 70-5.73) % of DW respectively. This study demonstrated that 3ml/litre Tetrapleura tetraptera aqueous inclusion for broilers was the most effective as it significantly influenced some carcass characteristics and organ weights as indicated above.